Peer Monitoring Book (PMB) Sebagai Solusi Perilaku Prokrastinasi Siswa di Masa Pandemi - Laila Sangadah; Viola Wulan Azzahro; Nurul Fadilah Tsani (Al Hikmah: Journal of Education, 2021)
The focus of the research is the application of the Peer Monitoring Book (PMB) method as a solution to overcome the students procrastination behaviour during Covid-19 pandemic. The research was carried out in Daarunnajah Boarding School of MAN 1 Magelang, Central Java. The approach used is a mixed mrthod that combines quantitative and qualitative approaches. Quantitative data collection technique used are questionaires, and for qualitative data use interviews and observations.The results showed that the application of the Peer Monitoring Book (PMB) method was effective and helped overcome the procrastination behavior of students at Daarunnajaah Girls Dormitory MAN 1 Magelang during the Covid-19 pandemic. Evidenced by the increased discipline of students in collecting school assignments.Fokus penelitian adalah penerapan metode Peer Monitoring Book (PMB) sebagai solusi mengatasi perilaku prokrastinasi siswa di masa pandemi Covid-19. Penelitian dilaksanakan di Asrama Putri Daarunnajaah MAN 1 Magelang Jawa Tengah. Pendekatan yang digunakan adalah campuran (mixed method) yang menggabungkan antara pendekatan kuantitatif dan kualitatif. Teknik pengumpulan data secara kuantitatif yang digunakan adalah angket atau kuesioner, sedangkan untuk kualitatif menggunakan wawancara dan observasi.Hasil Penelitian menunjukkan bahwa penerapan metode Peer Monitoring Book (PMB) efektif dan membantu mengatasi perilaku prokrastinasi siswa di Asrama Putri Daarunnajaah MAN 1 Magelang selama pandemi Covid-19. Dibuktikan dengan meningkatnya kedisiplinan siswa dalam mengumpulkan tugas-tugas sekolah.